Image Fusion Guided Device Closure of Left Ventricle to Right Atrium Shunt. Issue 14 (6th October 2015) - Grant, Elena K.; Faranesh, Anthony Z.; Cross, Russell R.; Olivieri, Laura J.; Hamann, Karin S.; O'Brien, Kendall J.; Hansen, Michael S.; Donofrio, Mary T.; Lederman, Robert J.; Ratnayaka, Kanishka; Slack, Michael C.
Abstract : Supplemental Digital Content is available in the text.